IoT furniture prototype 3 - Yong, Siang (2018)
In this 4th Generation era that introduces faster internet speed and wider network spectrum, it would be weird to not explore the many possibilities that the Internet can bring us to. Commonly known as IoT, the Internet of Things has been the technology that brings so much convenience to our daily lives. Looking around us, IoT has slowly entered into our daily lifestyles from smart home products such as television, mobile phones, cameras to driverless vehicles and in time to come, it will continue to bring more efficiencies and greater productivity to our lives and to the greater economy [1]. Due to campus expansion plans, these home-grown Acacia Trees were cut from Yun Nan Garden, Nanyang Technological University (NTU). Thus, there was an initiative to give these trees a second life to continue serving the NTU community. Instead of providing fresh air and making the Yun Nan Garden looking beautiful with its green features, these trees are turned into smart chairs with the addition of IoT. These smart chairs will be showcased in the NTU Alumni House to continue its purpose of serving the NTU community. The IoT Furniture Prototype 3 is a complete makeover from previous prototypes where it also introduces IoT but will fix on their imperfections using new hardware. The hardware used is a Arduino-compatible board called Wiolink. During this early stage of development, the focus is on capturing the duration of occupancy from a chair. A force sensing sensor will sense for occupancy. Duration of occupancy will be captured when someone sits on the chair. Thereafter, using the ESP8266 Wi-Fi function that the Wiolink offers, this data will be sent to the online cloud server - Thingspeak for capturing and analysis. Meanwhile, the exact data will be reflected in a newly developed website for interaction with the user. Apart from the showcasing element that is to be implemented in the NTU Alumni House located at Marina Square, the concept applied in the IoT Furniture Prototype 3 can be used in other applications. The applications are: 1) Hotel & Tourism Industries. When the chairs are placed around the hotel, it helps the hotel management to identify where are their popular spots are so that improvements can be made to be least interaction areas. By doing so, it creates a win-win situation because guests get to have a more enjoyable stay while the hotel continue to earn revenue from the improvements made. 2) Food & Beverage Industries. Restaurant management can get the data on the average dining time so that improvements can be made into making every dining experience a positive one for their customers. (eg. Provide accurate waiting time so customers do not waste time queue-ing.) 3) Elderly Care. Apart from using the sensor to detect chair occupancy, the sensor can also be used to provide an extra pair of eyes for healthcare specialists to look after their patients, especially to those that require special care (eg. Special care patients are not on their bed or chair but wander off.) This report aims to provide the detailed documentation on the project design, implementation, creating and testing of the website and the Arduino codes written that will be used to program the hardware to achieve its objectives.